PERTANGGUNGJAWABAN HUKUM NOTARIS DAN PPAT DALAM PEMBERIAN HAK TANGGUNGAN ATAS TANAH MILIK BERSAMA SECARA SEPIHAK - Aushi Aulia Rahmah; Rahayu Subekti; Noor Saptanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Deeds serve as perfect evidence, even though there is a possibility of error or negligence. Notaries are responsible for preparing Power of Attorney for Encumbering Rights (SKMHT), while Deed Officials Officer (PPAT) also bears responsibility in exercising their authority and obligations, particularly in the preparation of the Deed of Granting Mortgage Rights (APHT). This study aims to understand the responsibilities of Notaries and PPATs regarding deeds that have been revoked based on court decisions. The results of the analysis show that the responsibilities of Notaries in the preparation of SKMHT and PPAT in the preparation of APHT include checking documents, and both are responsible for the authenticity and validity of these documents. This study emphasizes that Notaries and PPAT are required to ensure legality and obtain approval from all parties involved in the granting of Mortgage Rights on jointly owned land. If they are negligent or intentionally certify deeds granting Mortgage Rights without valid consent, Notaries and PPATs may be held legally liable in civil, criminal, and administrative aspects.